Me. Rev. Stat. tit. 12, ch. 16, § 73 (1840) - (:unkn) unknown (My University, 1837)
Prohibited the enrollment of idiots, lunatics, common drunkards, vagabonds, paupers, nor any person convicted of any infamous crime, and anyone else besides white, abled bodied, male citizens into any office of the militia.
Keywords: MILITIAS